The development of crowdfunding in the United States: Case study of USA crowdfunding platforms - Fouzia, Boudhar; Meriem, Djamaa (The International tax journal, 2025)
In the United States, crowdfunding has focused mostly on individual needs. But when entire neighborhoods, towns, or issues need funding, options become fragmented– and the impact is often minimal in the age of social media, e-marketing, and digital transformation. This study shows that crowdfunding gives people the tools to mobilize support, unleash resources, and achieve results at scale. This technology believes in communities that support each other. Achieving the principle of equal investment opportunities to achieve economic development. Therefore, we will present the most important leading crowdfunding platforms in the United States ( kickstarter, indiegogo, rise up crowdfunding……)